Investigation of isotherms and isosteric heat of adsorption for PW11@HKUST-1 composite - Musa, S.G. (Academic Press Inc., 2022)
Impregnation of functional materials, such as polyoxometalates (POMs) into the pores of metal-organic frameworks (MOFs) is one approach to modifying their host-guest interactions. Although, the effect of this approach is well investigated in the fields of catalysis, luminescent materials, and biomedical imaging, still little is known about their gas adsorption properties. Isosteric heat of adsorption, (Qst) is one of the significant parameters in understanding the adsorption process for adsorbent materials. Here in we report the impregnation of a Keggin-type lacunary (PW11) nanoclusters into copper trimesic-based MOF of HKUST-1, to investigate the isotherms and isosteric heat of adsorption, for carbon dioxide calculated using the ClausiusâClapeyron equation. The PW11 brings Ï-accepting tendency and highly electronegative oxygen atoms on their surface to the HKUST-1 structure that selectively increases the affinity of HKUST-1 for CO2. This improves the Qst value for PW11@KUST-1 as compared with the pristine MOF. This study shows that the introduction of anionic metal-oxide of POMs can change the CO2 adsorption property of the MOF materials. Â© 2022 Elsevier Inc.